Dietary changes during the COVID-19 lockdown in Iranian households: are we witnessing a secular trend? A narrative review - Nikooyeh, Bahareh; Ghodsi, Delaram; Amini, Maryam; Rabiei, Samira; Rasekhi, Hamid; Motlagh, Mohammad Esmaeil; Neyestani, Tirang R. (Frontiers in Public Health, 2024)
The pandemic of coronavirus infection emerging in the late 2019 influenced almost all aspects of human life including food choices and dietary habits.: A web-based search was conducted during March-April 2024 in MEDLINE/PubMed, CINAHL, EMBASE, and Cochrane Library for published reports of largescale surveys on dietary changes during or shortly after coronavirus pandemic lockdown in Iran.The key words used were coronavirus OR COVID-19, diet OR nutrition, household and Iran.Those studies confined to an area, subgroups (like students) or just a city or province were not included. To track dietary changes from years before the lockdown, we used and plotted data from the Households Income and Expenditure Survey (HIES), Statistical Centre of Iran.The overall results of the nationwide studies during lockdown period in Iran revealed that consumption of milk, yogurt, cheese, red meat, white meat, eggs and rice/bread decreased in a sizeable proportion of the households. In about 47% of the households who had decreased their weekly consumption of animal protein sources, the intake of rice and bread had increased instead.Accordingly, 35% and 44% of the households reported decreased consumption frequency of fruits and snacks, respectively, with 21% of those with decreased fruit consumption completely removed fruits from their food baskets. Meanwhile, dietary supplement use especially vitamin D, vitamin C, zinc and multivitamin had increased in the households but mostly among those with higher incomes. Decreased income was a common reason for all these dietary changes which can have very serious health consequence in long term.In this review, we show evidence that these changes had already been started years before the pandemic and presumably have not been back to pre-pandemic situation yet. Finally, we suggest some strategies for policymakers to overcome the crisis and enhance community nutrition and health.